Lithium Toxicity in the Setting of Nonsteroidal Anti-Inflammatory Medications - Syed Hassan; Fatima Khalid; Zaid Alirhayim; Syed Amer (Case Reports in Nephrology)
Lithium toxicity is known to affect multiple organ systems, including the central nervous system. Lithium levels have been used in the diagnosis of toxicity and in assessing response to management. There is evidence that nonsteroidal anti-inflammatory medications (NSAIDs) can increase lithium levels and decrease renal lithium clearance. We present a case of lithium toxicity, which demonstrates this effect and also highlights the fact that lithium levels do not correlate with clinical improvement, especially the neurological deficit.